2015
DOI: 10.1016/j.phrs.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

One-week administration of hydroxytyrosol to humans does not activate Phase II enzymes

Abstract: The notion that (poly)phenols act as direct free radical scavengers is being challenged by mere chemical and biochemical considerations such as bioavailability and intracellular concentrations. An alternative hypothesis that is gaining considerable traction is that (poly)phenols are processed by the body as xenobiotics via the Keap1/Nrf2/ARE signaling axis, leading to the induction of Phase II enzymes. However, there are no solid human data to confirm this interesting supposition. In this study, we tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…Several in vitro studies using humans cells and animal in vivo studies investigating olive polyphenols have supported Nrf2 activation and its consequential expression of protective genes [72,94]. Conversely, a recent human intervention study has shown no evidence of altered phase II enzyme expression (the downstream product of Nrf2 activation) in peripheral blood mononuclear cells following consumption of HT (5 mg and 25 mg per day in olive mill waste water) [95]. The olive mill waste water was tested to confirm oleuropein was not present.…”
Section: Ole and Evidence Of The Ability Of Olive Leaf Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro studies using humans cells and animal in vivo studies investigating olive polyphenols have supported Nrf2 activation and its consequential expression of protective genes [72,94]. Conversely, a recent human intervention study has shown no evidence of altered phase II enzyme expression (the downstream product of Nrf2 activation) in peripheral blood mononuclear cells following consumption of HT (5 mg and 25 mg per day in olive mill waste water) [95]. The olive mill waste water was tested to confirm oleuropein was not present.…”
Section: Ole and Evidence Of The Ability Of Olive Leaf Polyphenolsmentioning
confidence: 99%
“…Oleuropein in a human in vitro model has also been shown to activate Nrf2 and HO-1 expression [99]. However, in vivo human trials with HT have failed to find an up-regulation of phase 2 enzymes which are the by-product of EpRE and Nrf2 stimulation [95]. …”
Section: Ole and Evidence Of The Ability Of Olive Leaf Polyphenolsmentioning
confidence: 99%
“…Samples analyzed were obtained from a previous intervention study [9]. This work is registered at ClinicalTrials.gov (identifier: NCT02273622).…”
Section: Human Studiesmentioning
confidence: 99%
“…To evaluate whether the selected HT-modulated miRNAs observed in the animal supplementation studies were also modulated in humans, we investigated the effects of HT supplementation (25 mg/ day) in a double-blind, randomized, placebo-controlled trial (NCT02273622) [9]. One-week supplementation with HT resulted in a within-group increase in the expression of miR-193a-5p in PBMCs (Fig.…”
Section: Mir-193a-5p Is Modulated By Ht Supplementation In Healthy Sumentioning
confidence: 99%
See 1 more Smart Citation